2021
DOI: 10.1155/2021/4582412
|View full text |Cite
|
Sign up to set email alerts
|

Update on Pharmacological Activities, Security, and Pharmacokinetics of Rhein

Abstract: Rhein, belonging to anthraquinone compounds, is one of the main active components of rhubarb and Polygonum multiflorum. Rhein has a variety of pharmacological effects, such as cardiocerebral protective effect, hepatoprotective effect, nephroprotective effect, anti-inflammation effect, antitumor effect, antidiabetic effect, and others. The mechanism is interrelated and complex, referring to NF-κB, PI3K/Akt/MAPK, p53, mitochondrial-mediated signaling pathway, oxidative stress signaling pathway, and so on. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 84 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…Physcion has a moderate intestinal permeability with P eff values of (3.32 ± 1.50) × 10 –3 (2.30 ± 1.57) × 10 –3 (2.40 ± 0.58) × 10 –3 , and (7.45 ± 3.30) × 10 –3 cm/min in the duodenum, jejunum, ileum, and colon, respectively ( Wang P. et al, 2011 ). Rhein is mostly administered orally due to its low solubility, although achieving a stable and effective blood concentration is difficult ( Li et al, 2021 ). The components detected in the plasma gradually increased as the dose increased.…”
Section: Resultsmentioning
confidence: 99%
“…Physcion has a moderate intestinal permeability with P eff values of (3.32 ± 1.50) × 10 –3 (2.30 ± 1.57) × 10 –3 (2.40 ± 0.58) × 10 –3 , and (7.45 ± 3.30) × 10 –3 cm/min in the duodenum, jejunum, ileum, and colon, respectively ( Wang P. et al, 2011 ). Rhein is mostly administered orally due to its low solubility, although achieving a stable and effective blood concentration is difficult ( Li et al, 2021 ). The components detected in the plasma gradually increased as the dose increased.…”
Section: Resultsmentioning
confidence: 99%
“…There is little doubt that rhein can reversibly bind to FTO and inhibit m 6 A demethylation in vitro [817]; however, rhein is not a selective inhibitor of m 6 A "erasers" that include the ALKB family proteins [818]. Furthermore, rhein is a natural product with an impressive array of pharmacological activities [819], including antiviral mechanisms. Rhein can significantly inhibit IAV adsorption and replication via antioxidant-dependent pathways in vitro [820].…”
Section: Is M 6 a A Positive Or Negative Regulator Of Sars-cov-2 Repl...mentioning
confidence: 99%
“…have extensive protective effects on various targets of renal fibrosis, there are also certain limitations. For example, some natural ingredients have poor solubility, low bioavailability, poor intestinal absorption, strong dose dependence when intervening in some targets, hepatotoxicity and nephrotoxicity ( Dong et al, 2016 ; Xie et al, 2019 ; Dong et al, 2020 ; Li et al, 2021 ). Most of the above conclusions are based on animal experiments, and there is a lack of their use in clinical practice.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Modern pharmacological studies have found that rhein has anti-inflammatory, antitumor and antifibrotic effects and has certain protective effects in the liver and kidneys. The molecular schematic diagram of rhein is shown in Figure 4 ( Sun H. et al, 2016 ; Li et al, 2021 ). Chrysophanol is derived from Polygonaceae plants.…”
Section: Modern Pharmacological Studies Of Natural Components In ...mentioning
confidence: 99%